Rethinking the tendering frameworks of construction contractors in the context of a soft systems methodology approach - Urquhart, Stephen; Whyte, Andrew (HIGHER EDUCATION PRESS, 2018)
Limited research has been conducted on the internal tendering procedures (ITP) of construction contractors because of the commercially sensitive and confidential nature of the subject matter. This limitation explains the reluctance of contractors to undergo interviews. Existing research (outside bid/no-bid and margin decision factor identification and subsequent decision modeling development) only begins to provide insights into key tendering stages, particularly around risk assessments and corporate review processes. Early research suggested one to three review stages. However, when considering the whole work procurement process from prospect identification to contract execution, five to seven series of reviews can be arguably applied by some contractors, wherein some reviews stepped through several layers of internal senior management. Tendering processes were presented as flowchart models that traditionally follow “hard” system (rectangular shapes and straight line arrows) steps, which suggest that a precise process also leads to precise results. However, given that contractors do not win every tender they submit, the process is less precise than that suggested in rigidly structured flowcharts. Twenty-five detailed semi-structured interviews were held with purposely selected high-profile publicly and privately owned construction companies in Australia with significantly varied turnovers. Analyses show that contractors are concerned about the negative effects of increasing corporate governance demands, with many stating that people involved are the most critical element to tendering success. A new way of presenting the ITP of contractors is assessed using a soft systems methodology (SSM) approach. SSM offers an alternative way of considering human interaction challenges within the ITP of contractors, which needs to be tested with the industry. The format graphics of SSM guidelines are presented as a way of offering contractors a different approach, which may assist individuals who are looking to re-structure their tendering activities in a more humanistic and less rigid procedural approach.